Studi komperatif teori among dan zona proximal development dalam pembelajaran sekolah dasar - Mas Rukhin Lubabul Huda (Indonesian Journal of Learning and Educational Studies, 2025)
The purpose of this study is to compare Among's theory and Vygotsky's Zone of Proximal Development theory by comparing and providing similarities and differences between the two theories. Both theories were proposed by Ki Hajar Dewantara and Vygotsky, two figures who discussed the concept of a social approach to learning. This research uses a qualitative method with a literature study approach from Ki Hajar Dewantara's perspective on Among Theory and Vygotsky's ZPD theory. The research data is sourced from various books, articles, and accurate information sources. The analysis technique in this research is a comparative study discussing the similarities and differences between the two figures. The results of the reserarch data are: 1) Ki Hajar Dewantara's theory of Among uses the concept of Among, which is divided into Asah, Asih, and Asuh, applied to the learning process, 2) Vygotsky's theory of Zone Proximal Development (ZPD) is related to Scaffolding, which requires interaction between students and teachers with good language skills. 3) Application in primary education, namely the social role in assisting the learning process, such as guidance from teachers and students, students learning in groups, and parental guidance when studying at home. This research contributes by summarizing the concepts of Among and ZPD theories regarding the concepts of the two figures and analyzing their similarities and differences.